MEDIA SOSIAL BAGI PENERIMAAN DIRI, HARGA DIRI DAN KEBAHAGIAAN REMAJA: APAKAH AKAN MERUSAK ATAU MEMBANGUN? - Mariagoretti Sinta Meilana (Prodi Bimbingan dan Konseling, Fakultas Keguruan dan Ilmu Pendidikan, UKI, Jakarta, 2021)
Technological advances in the are of emergence of social media inadvertently shape the pattern of human socialization. Youth show who they are and there is a sense of openness in expressing themselves on social media. Social media users are widely presented on the appearance of ideal self-presentation and this has the potential to harm adolescent self-esteem. Methods: Literary Studies e-Journal obtained through seven electronic databases SocarXIV, Press/New Harbinger Publication, Pijar Psychology, Google Scholar, Springer Link, Science Direct, and SAGE Journals. The search was limited to English and Indonesian articles published since 2011. Results: There were three main findings identified in social media for self-acceptance, and destructive adolescent self-esteem and happiness, e.g. (1)Unacceptance (2)Low Self Esteem, (3)Unhappy. There are three main findings identified in social media for self-acceptance, self-esteem ad contructive adolescent happiness, e.g. (1) Self-Acceptance, (2)Self Esteem, (3)Happiness. Conclusion: Based on this literature riview, that social media for self-acceptance, self-esteem, and happiness of adolescent has the most damaging effects compared to those that builid self-acceptance, self-esteem, and happiness of adolescents.